INFLUENCE OF PEAK HEIGHT VELOCITY ON AGILITY AND SPRINT PERFORMANCE IN YOUNG PENCAK SILAT ATHLETES : A CROSS -SECTIONAL STUDY - Sari, Fenny Novita; Sumartiningsih, Sri (Journal of Physical Education and Sports, 2025)
This cross-sectional study examined the influence of Peak Height Velocity (PHV) on agility and sprint performance in young pencak silat athletes. 20 athletes (11 females, 9 males; aged 11-15 years) underwent anthropometric assessments to estimate PHV using the Mirwald equation, with agility and sprint performance evaluated through the Illinois Agility Test and 20-meter sprint, respectively. Results revealed a significant negative correlation between PHV and agility (r = -0.458, p = 0.042), indicating that improved agility was associated with advancing maturation. At the same time, PHV showed a strong positive association with sprint performance (r = 0.650, p = 0.002). Male athletes demonstrated superior agility compared to females (p = 0.012), though no significant gender difference emerged in sprint times (p = 0.064). The findings establish PHV as a critical determinant of physical performance in adolescent pencak silat practitioners, with the maturation stage significantly influencing sport-specific skill development. These results emphasize the importance of incorporating biological maturation metrics, rather than relying solely on chronological age when designing training programs for youth martial artists. Coaches should consider athletes' PHV status to optimize agility and speed development while mitigating injury risks during growth spurts. The study provides empirical support for maturation-adjusted training protocols in combat sports, though longitudinal research is recommended to track performance trajectories across PHV phases and further validate these findings.